Genetic Tracing of Jatropha curcas L. from Its Mesoamerican Origin to the World - Li, Haiyan; Tsuchimoto, Suguru; Harada, Kyuya; Yamasaki, Masanori; Sakai, Hiroe; Wada, Naoki; Alipour, Atefeh; Sasai, Tomohiro; Tsunekawa, Atsushi; Tsujimoto, Hisashi; Ando, Takayuki; Tomemori, Hisashi; et al. (Frontiers in Plant Science, 2017)
Jatropha curcas L. (Jatropha), a shrub species of the family Euphorbiaceae, has been recognized as a promising biofuel plant for reducing greenhouse gas emissions. However, recent attempts at commercial cultivation in Africa and Asia have failed because of low productivity. It is important to elucidate genetic diversity and relationship in worldwide Jatropha genetic resources for breeding of better commercial cultivars. Here, genetic diversity was analyzed by using 246 accessions from Mesoamerica, Africa and Asia, based on 59 simple sequence repeat markers and eight retrotransposon-based insertion polymorphism markers. We found that central Chiapas of Mexico possesses the most diverse genetic resources, and the Chiapas Central Depression could be the center of origin. We identified three genetic groups in Mesoamerica, whose distribution revealed a distinct geographic cline. One of them consists mainly of accessions from central Chiapas. This suggests that it represents the original genetic group. We found two Veracruz accessions in another group, whose ancestors might be shipped from Port of Veracruz to the Old World, to be the source of all African and Asian Jatropha. Our results suggest the human selection that caused low productivity in Africa and Asia, and also breeding strategies to improve African and Asian Jatropha. Cultivars improved in the productivity will contribute to expand mass commercial cultivation of Jatropha in Africa and Asia to increase biofuel production, and finally will support in the battle against the climate change.